2013
DOI: 10.1128/aem.02939-12
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Environmental Persistence of the Causative Agent of White-Nose Syndrome, Geomyces destructans, in Bat Hibernacula of the Eastern United States

Abstract: White-nose syndrome (WNS) is an emerging disease of hibernating bats caused by the recently described fungus Geomyces destructans. First isolated in 2008, the origins of this fungus in North America and its ability to persist in the environment remain undefined. To investigate the correlation between manifestation of WNS and distribution of G. destructans in the United States, we analyzed sediment samples collected from 55 bat hibernacula (caves and mines) both within and outside the known range of WNS using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
163
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(167 citation statements)
references
References 25 publications
4
163
0
Order By: Relevance
“…The pathogen that causes WNS, Pseudogymnoascus destructans, is a cold growing fungus that infects bats' skin during their hibernation period [19][20][21], and can persist in the environment for long periods of time in the absence of bats [22,23]. The resulting infections lead to the disruption of homeostatic processes and ultimately mortality [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen that causes WNS, Pseudogymnoascus destructans, is a cold growing fungus that infects bats' skin during their hibernation period [19][20][21], and can persist in the environment for long periods of time in the absence of bats [22,23]. The resulting infections lead to the disruption of homeostatic processes and ultimately mortality [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Lorch et al (2013) found that the probability of detecting Pd in a Pd-positive hibernaculum was 56 % for each sample using real-time PCR, compared to 14% using culture-dependent methods.…”
Section: Introductionmentioning
confidence: 99%
“…DNA from various organisms is able to persist long term in the environment, as shown by its recovery from paleontological remains, but the limit of persistence of non-viable Pd DNA in bat hibernacula is unknown. Viable Pd is known to persist in hibernacula soil in the absence of bats (Lorch et al, 2013), and it may be able to propagate as a saprobe (Raudabaugh and Miller, 2013). Reynolds et al (2015) successfully grew Pd on a variety of sterilized sediments from caves in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bat-inhabited caves can be reservoirs of human pathogenic fungi such as Histoplasma capsulatum, causative agent of histoplasmosis (Cano & Hajjeh, 2001), which is frequently isolated from warm caves in tropical areas. In addition, the sudden and catastrophic appearance of the White Nose Syndrome (WNS), caused by Pseudogymnoascus destructans, in cave-dwelling North American bats in 2006 has stimulated interest in cave fungi in the last few years (Blebert et al, 2009;Lorch et al, 2013). A huge bat colony of more than 2,000 individuals spends the winter in Magura Cave.…”
Section: Introductionmentioning
confidence: 99%